Exploring the effects of algorithm-driven news sources on political behavior and polarization. (March 2021) - Feezell, Jessica T.; Wagner, John K.; Conroy, Meredith
Abstract: Do algorithm-driven news sources have different effects on political behavior when compared to non-algorithmic news sources? Media companies compete for our scarce time and attention; one way they do this is by leveraging algorithms to select the most appealing content for each user. While algorithm-driven sites are increasingly popular sources of information, we know very little about the effects of algorithmically determined news at the individual level. The objective of this paper is to define and measure the effects of algorithmically generated news. We begin by developing a taxonomy of news delivery by distinguishing between two types of algorithmically generated news, socially driven and user-driven, and contrasting these with non-algorithmic news. We follow with an exploratory analysis of the effects of these news delivery modes on political behavior, specifically political participation and polarization. Using two nationally representative surveys, one of young adults and one of the general population, we find that getting news from sites that use socially driven or user-driven algorithms to generate content corresponds with higher levels of political participation, but that getting news from non-algorithmic sources does not. We also find that neither non-algorithmic nor algorithmically determined news contribute to higher levels of partisan polarization. This research helps identify important variation in the consequences of news consumption contingent on the mode of delivery. Highlights: Non-algorithmic/algorithmic news impact pol. behavior and polarization differently. Using algorithmically generated news sources leads to higher political participation. Non-algorithmic news sources fail to predict political participation. Neither algorithmic nor non-algorithmic news sources impact political polarization.